Use of digital assessment tools to measure health facility readiness to provide the WHO recommended package of care for lymphatic filariasis morbidity - Bougma, Windtaré Roland; Aiogalé, Victorino Martinho; Attoumbre, Bienvenu Yao; Bartlett, Sarah; Brahima, Kouma; Coulibaly, Mamadou; Coulibaly, Yaya Ibrahim; Dicko, Boubacar Morou; D’Souza, Susan; Doumbia, Salif Seriba; Gargannah, Gar Mondyu; Musa, Balla; et al. (Frontiers in Tropical Diseases, 2024)
BackgroundA country claiming to have achieved elimination of Lymphatic filariasis (LF) as a public health problem must undergo and document a quality assessment of the World Health Organization (WHO) recommended essential package of care for patients with lymphedema and hydrocele. This must be done in at least 10% of facilities offering services. In Liberia, Côte d’Ivoire, Mali and Guinea-Bissau the LF programmes used the Hydrocele Facility Assessment Tool (HFAT) and the Lymphedema Facility Assessment Tool (LFAT) to provide an objective assessment of facilities providing LF morbidity management services. Information gathered through these tools is used to improve service delivery and document the number of implementation units with at least one facility providing the essential package of care in the WHO epidemiological reporting form (EPIRF). The development of the HFAT and LFAT digital tools were informed by WHO’s direct inspection protocol (DIP) for lymphedema, WHO’s service availability and readiness assessment (SARA), and WHO’s situational analysis to assess emergency and essential surgical care.MethodsBetween May 2022 and January 2023, 33 hydrocele facility assessments and 102 lymphedema facility assessments were implemented in these four countries. Facility and indicator score benchmarks were set at 75%.ResultsThe LFAT and HFAT indicator results were variable both within and between countries. 26 (79%) facilities scored 75% or better on the assessment for hydrocele surgery and 15 (15%) facilities scored 75% or better on the assessment for lymphedema. Examples of indicators with significant need for quality improvement actions were 1) LFAT indicator ‘Trained staff - Community Health Care Providers trained in lymphoedema management’ which did not achieve the 75% benchmark in any of the countries; 2) HFAT indicator on use of surgical safety checklist which only achieved the 75% benchmark in Liberia.DiscussionThe discussion highlights the current challenges faced by endemic countries to ensure that an essential package of care (of sufficient quality) for lymphedema management and hydrocele surgery is available.